A smart material for the in situ detection of mercury in fish. Issue 80 (15th September 2016) - García-Calvo, José; Vallejos, Saúl; García, Félix C.; Rojo, Josefa; García, José M.; Torroba, Tomás
Abstract : A new polymeric sensing material acts as a smart label for the fluorescent detection of Hg 2+ and MeHg + in fish samples. Abstract : We have developed a new fluorogenic polymer capable of detecting the presence of mercury contamination in fish samples. The modified polymer emits blue light when irradiated with UV light proportional to the quantity of mercury, as MeHg + or Hg 2+, present in fish. The quantitative relation between the concentration of mercury in fish and the increase of fluorescence in the polymer in contact with fish samples was confirmed, giving rise to quick and reliable results in the measurements of the presence of mercury in fish using a portable fluorogenic polymeric probe.